Effect of fan placement on milk production and dry matter intake of lactating dairy cows housed in a 4-row freestall barn - John F. Smith; Joseph P. Harner; S.E. DeFrain; Michael J. Brouk (Kansas Agricultural Experiment Station Research Reports, 2001)
Heat stress reduces milk production, feed intake, and reproductive efficiency each summer in Kansas. Without heat abatement procedures, milk production may decline 20- 30% during the summer months. Research has shown that supplemental fan cooling in combination with low pressure feedline sprinklers can reduce the effects of heat stress on milk production and feed intake. One critical issue in heat stress abatement is the location of fans in a 4-row freestall barn. Research conducted during the summer of 2000 on a northeast Kansas dairy found that locating fans over both the feedline and head-to-head freestalls increased milk production 5.8 lb/cow/d and reduced respiration rates in the morning and at night compared to mounting fans only over the feedline. Pen feed intakes also tended to be greater when fans were located in both areas. Economic analysis showed that after accounting for cost associated with ownership, operation, and increased feed intake, net farm income was estimated to be increased by $3,600- 6,600 for a pen of 84 cows. A 100-cow Kansas dairy could increase farm profits by $8,000 if these heat abatement techniques were utilized. Location of fans over both the feedline and freestalls in combination with a low pressure feedline sprinkling system is an effective heat stress abatement strategy in 4- row freestall barns.; Dairy Day, 2001, Kansas State University, Manhattan, KS, 2001;
Keywords: Dairy Day; 2001; Kansas Agricultural Experiment Station contribution; no. 02-133-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 881; Dairy; Heat stress; Cow comfort; Cow cooling